Comparison of Chest Computed Tomography Differential Diagnosis of Ground Glass Opacities in the COVID-19 Patients - Inayatullah, Imran Khan Memon, Muhammad Rashid Rasul, Bhagwan Das, Din Muhammad Sohu, Akhtar Hussain Phul, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare chest computed tomography (CT) diagnosis of ground glass opacities in the COVID-19 patients. Study design: Retrospective study. Place and duration of study: Department of Radiology, Ghulam Muhammad Mahar Medical College Sukkur from 1st July 2020 to 31 August 2021. Methodology: Fifty patients on differential CT diagnosis of ground glass opacities seen in COVID 19 patients were enrolled. Thoracic CT images by applying auto exposure-control settings and ranges of scan were done. The noise-index was kept as 12.3. Using helical 16 slice Alexion CT-Toshiba. Keeping a comparison with viral infection CT images a list of 7 signs which were positive for Covid CT scan were recorded. Peripheral lesions meant any lesions which effects peripheral area up to 3 to 4 cm lung periphery with/without having central dispersal. A hazy-opacity was termed as ground glass. Results: Mean age of the patients was 49.1±10.2 years with 27 (54%) males and 23(46%) females. Mix ground glass opacitites and consolidation were also the features of the CT imaging in coronavirus posisitve cases. Man-Whitney test results showed that combined-CT scoring had a SE value as 0.044 with a confidence interval between 0.756-0.927. Comparing the differential CT values within COVID and non COVID patients based on RT PCR results it was observed that posterior region lower lobe involvement was a feature of COVID-19 patients while crazy paving pattern and peripheral distribution was also seen in corona patients. Conclusion: Present study highlights that chest CT helps in differentitaing corona virus from other causes of pneumonias and grond glass opacities.